On the Life Cycle and Natural History of Hymenitis Nero (Lepidoptera: Ithomiinae) in Costa Rica - Allen M. Young (Psyche: A Journal of Entomology)
A knowledge of life cycle and natural history are often important prerequisites to studies of population biology in butterflies. Although studies on the systematics and broad distribution patterns of that familiar New World Tropical group, the Ithomiinae, have been conducted (Seitz, 194; Fox, 1956; Fox, 1968), a lot remains to be known about the biology of many species in Central America. This is surprising in light of the considerable interest in these butterflies as members of mimicry complexes. In this spirit, this paper summarizes life cycle and natural history data on a clear wing ithoreiine Hymenitis nero (Hewitson) (Nymphalidae: Ithomiinae) in Costa Rica. Similar studies of several other sympatric ithomiines have either been completed (Young, in prep.) or begun, as a preliminary step towards understanding the local patterns of diversity of this family in selected tropical plant communities.